2013
DOI: 10.1186/1471-2393-13-141
|View full text |Cite
|
Sign up to set email alerts
|

Maternal near miss and mortality in a rural referral hospital in northern Tanzania: a cross-sectional study

Abstract: BackgroundMaternal morbidity and mortality in sub-Saharan Africa remains high despite global efforts to reduce it. In order to lower maternal morbidity and mortality in the immediate term, reduction of delay in the provision of quality obstetric care is of prime importance. The aim of this study is to assess the occurrence of severe maternal morbidity and mortality in a rural referral hospital in Tanzania as proposed by the WHO near miss approach and to assess implementation levels of key evidence-based interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
109
8
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(158 citation statements)
references
References 32 publications
29
109
8
8
Order By: Relevance
“…The treatments provided in the study setting were also accessible for a few proportions of mothers due to their low income and lack of resources in the particular setting. This reasons were also observed in studies performed in rural areas of northern Tanzania and Uganda (18,19).…”
Section: Discussionsupporting
confidence: 52%
“…The treatments provided in the study setting were also accessible for a few proportions of mothers due to their low income and lack of resources in the particular setting. This reasons were also observed in studies performed in rural areas of northern Tanzania and Uganda (18,19).…”
Section: Discussionsupporting
confidence: 52%
“…Our study showed a statistically significant association between the pregnancy state on ICU admission and outcome: 10.9% of the women admitted after delivery died compared with only 5.2% of those admitted during pregnancy. These results are in agreement with studies in India and Tanzania (2013) (27,28). These results may be due to the higher incidence of sepsis in the postpartum period following surgical caesarean delivery or as a complication of postpartum haemorrhage.…”
Section: Boxsupporting
confidence: 83%
“…The maternal near-miss mortality ratio was 10.8:1 and the mortality index was 8.5%. These indicators are similar to those reported in studies in Tanzania and Malawi where the range was 5-12:1 (28,30). On the other hand, very high ratios of 117-223:1 were reported in studies from Western Europe which used similar case definition criteria (22,31).…”
Section: Boxsupporting
confidence: 78%
“…The prevalence of near-miss case in this study was 2.4%. The demographic characteristics of the women classified as near-miss was median age-27 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), 138 (28.7%) women were nulliparous. Majority of them were pare 1-2.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Jayarathnam et al documented a ratio of 6 per 1000 live births. 30,[30][31][32][33][34][35][36] …”
Section: Discussionmentioning
confidence: 99%